Manufacture and optimization of nanostructured Cr-Al-N coatings produced by reactive magnetron sputtering - Avila, Pedro Renato Tavares (2021)
Deposition of ceramic hard coatings are paramount in surface engineering as a strategy for protecting metallic surfaces of severe wear, many times present in industrial applications. Among the options of materials for this purpose, the transition metal nitrides are some of the most common. Cr-Al-N present interesting mechanical and anti-oxidation properties. Along with the choice of materials, the route of deposition is a major parameter to be taken in consideration and thoroughly studied to optimize the performance of the film solution. In this thesis, Cr-Al-N coatings were deposited over stainless steel substrate using dcMS and HiPIMS and its impact on the properties of the films were investigated. The coatings presented high concentration of N, possibly due to target poisoning during reactive depositions. The samples produced using 70/30 at % target exhibited better mechanical performance as consequence of the larger amount of Al in solid solution. HiPIMS films presented improved properties and densification caused by the higher ionization and consequently higher energy in comparison with dcMS manufactured samples. The nitride coatings were produced using a novel technique in which the substrate is oscillated continuously in front of the target to produce nanostructured coatings by varying the angle of incidence of the sputtered material. This technique named Dynamic Glancing Angle Deposition (DGLAD) was found responsible for creating misorientation gradients along the grains. These features combined with the zigzag shape of grain boundaries contributed to enhancement in hardness and wear resistance, especially when larger oscillatory ranges were used. DGLAD is proved as a technique capable of positively influence microstructure, deposition rate and mechanical performance of the Cr-Al-N coatings.